Moraxella catarrhalis Binds Plasminogen To Evade Host Innate Immunity - Singh, Birendra (Infect Immun, 2015)
Several bacterial species recruit the complement regulators C4b-binding protein, factor H, and vitronectin, resulting in resistance against the bactericidal activity of human serum. It was recently demonstrated that bacteria also bind plasminogen, which is converted to plasmin that degrades C3b and C5. In this study, we found that a series of clinical isolates (n = 58) of the respiratory pathogen Moraxella catarrhalis, which is commonly isolated from preschool children and adults with chronic obstructive pulmonary disease (COPD), significantly binds human plasminogen. Ubiquitous surface protein A2 (UspA2) and hybrid UspA2 (UspA2H) were identified as the plasminogen-binding factors in the outer membrane proteome of Moraxella. Furthermore, expression of a series of truncated recombinant UspA2 and UspA2H proteins followed by a detailed analysis of protein-protein interactions suggested that the N-terminal head domains bound to the kringle domains of plasminogen. The binding affinity constant (K(D)) values of full-length UspA2(30–539) (amino acids 30 to 539 of UspA2) and full-length UspA2H(50–720) for immobilized plasminogen were 4.8 × 10(−8) M and 3.13 × 10(−8) M, respectively, as measured by biolayer interferometry. Plasminogen bound to intact M. catarrhalis or to recombinant UspA2/UspA2H was readily accessible for a urokinase plasminogen activator that converted the zymogen into active plasmin, as verified by the specific substrate S-2251 and a degradation assay with fibrinogen. Importantly, plasmin bound at the bacterial surface also degraded C3b and C5, which consequently may contribute to reduced bacterial killing. Our findings suggest that binding of plasminogen to M. catarrhalis may lead to increased virulence and, hence, more efficient colonization of the host.